Hubungan panjang tungkai dengan power otot tungkai pada siswa ekstrakurikuler bola basket di jombang - Alfian Maulana; Prisca Widiawati; Muhammad Putra Ramadhan (Physical Education Departement of University PGRI Jombang, 2025)
Basketball requires explosive lower limb muscle power to support jumping, acceleration, and rapid changes of direction. One factor suspected to influence this ability is anthropometric characteristics, particularly leg length. This study aimed to analyze the relationship between leg length and lower limb muscle power among basketball extracurricular students at SMAN 3 Jombang. This research used a quantitative approach with a correlational design. The sample consisted of 24 students aged 16–17 years selected through purposive sampling. Leg length was measured using an anthropometric measuring tape from the Spina Iliaca Anterior Superior (SIAS) to the medial malleolus, while lower limb muscle power was assessed using the vertical jump test calculated with the Sargent Jump formula. Data analysis included descriptive statistics, assumption tests, Spearman correlation, and regression analysis with interaction to examine the moderating role of sex. The results showed that among male students there was no significant relationship between leg length and vertical jump, whereas among female students the relationship was strong and significant. However, regression analysis indicated that leg length, sex, and their interaction did not show a significant partial effect on vertical jump performance. These findings indicate that leg length is not the sole determinant of lower limb muscle power, as other factors such as muscle strength, neuromuscular coordination, and movement technique also play important roles. This study provides contributions to school sports development, particularly in designing training programs and implementing talent identification based on athletes’ physical characteristics.